Evolution and governance of the biotechnology and pharmaceutical industry of China - Wang, K.; Hong, J.; Marinova, Dora; Zhu, L. (Elsevier Science, 2009)
The high-speed growth of China’s biotechnology industry during the past 20 years presents an excellent opportunity to examine its overall evaluation and governance from the perspective of science and technology policies. Although China’s biotechnology industry has achieved tremendous extension both in scale and structure, the strengths it has gained from achievements in research and development activities have been significantly weakened in relation to processes of commercialization. After examining the definition of China’s biotechnology industry as well as its evolution, the authors of this paper employ Actor-Networks Theory as a basic theoretical framework to reveal how China’s biotechnology industry develops in the form of evolving networks within the country’s social context and to identify what kinds of relationships exist among the relevant factors. Our hope is to provide guiding insights for improving the governance of China’s biotechnology industry both in policy and in management practices.